Cassava breeding and varietal dissemination in the Philippines: Major achievements during the past 20 years - Mariscal, Algerico M.; Bergantin, Reynaldo V.; Troyo, Anita D. (International Center for Tropical Agriculture, 2001)
During the past 20 years of close collaboration with CIAT in the cassava breeding program in the Philippines, much has been achieved, not only in terms of human capacity building but also in the acquisition of improved cassava germplasm. These materials were used in a multy-year selection scheme, which culminated in the release of several improved cassava varieties recommended for cultivation in the country, in order to support the need for food, feed and various industrial products. Since 1982 a total of 40,809 cassava hybrid seeds were received from CIAT headquarters in Colombia and 11,280 hybrid seeds rom the Thai-CIAT cassava program. These were evaluated in all stages of selection under Philippine conditions. Three cassava varieties were released by the Center during the early years of establishment and 16 varieties were subsequently released by the National Seed Industry Council. From these released varieties, six are of local origin, eight are from CIAT materials and five from locally developed hybrids. Progress in the selection of the materials received has been quite positive, meaning that a lot of the elite genetic materials introduced were selected for possible varietal release or as parental material for the breeding program. Considering the source of the two genetic populations we received, it was noted that hybrid seeds from Thailand performed very well in the Philippines; in fact, some of the elite materials have superior characteristics compared to the best Philippine varieties. About 0.15% of hybrid seeds received from CIAT/Colombia were eventually selected and maintained, while about 0.38% of seed received from the Thai-CIAT program were maintained for further trials and possible varietal release. The dissemination of new cassava varieties has been intensified during recent years through the conducting of adaptation trials in various parts of the country in collaboration with farmers and individuals in the private sector. The involvement of the private sector in the industrial use of cassava for processing into various products has triggered widespread planting of the new cassava varieties. San Miguel Corporation has promoted the planting of cassava for production of animal feeds and for alcohol, to be used in the manufacture of gin, a popular alcoholic drink in the Philippines. In 1997, about 5,000 hectares were planted to cassava primarily using Lakan and Golden Yellow varieties. New clones, KU-50, Rayong 5 and PSB Cv-12 (SM972-20) are rapidly being multiplied to provide part of the planting materials required for San Miguel’s cassava project expansion in Negros Occidental. In addition to this, starch factories continuously plant high yielding cassava (VC-5) for the starch industry. Starch factories now have an approximate combined area of 10,000 hectares of cassava planted to the recommended cassava varieties. Future breeding work and selection will focus on the identification of superior varieties, not only with high yield but with high starch content, tolerance to existing pests and diseases, and other characters that will satisfy the requirements of the cassava-based industry.